2001
DOI: 10.1182/blood.v97.6.1598
|View full text |Cite
|
Sign up to set email alerts
|

Impact of donor type on outcome of bone marrow transplantation for Wiskott-Aldrich syndrome: collaborative study of the International Bone Marrow Transplant Registry and the National Marrow Donor Program

Abstract: Multivariate proportional hazards regression was used to compare outcome by donor type and identify other prognostic factors. Most transplant recipients were younger than 5 years (79%), had a pretransplantation performance score greater than or equal to 90% (63%), received pretransplantation preparative regimens without radiation (82%), and had non-Tcell-depleted grafts (77%). Eighty percent received their transplant after 1986. The 5-year probability of survival (95% confidence interval) for all subjects was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
170
1
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(179 citation statements)
references
References 28 publications
1
170
1
7
Order By: Relevance
“…In the previous reports, T-cell depletion or CD34-positive selection was often performed in order to prevent GVHD when unrelated donor marrow was selected [18,20]. However, we did not use either method for our patients because they are sometimes associated with a risk of graft rejection and EBV-associated posttransplant lymphoproliferative disease (PTLD) when transplanting the immunodeficiency patients [11]. As GVHD in our series were relatively well controlled except for one case (Patient 2), we believe that HLAmatched unrelated donor marrow transplant can be safely performed without T-cell depletion or CD34-positive selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous reports, T-cell depletion or CD34-positive selection was often performed in order to prevent GVHD when unrelated donor marrow was selected [18,20]. However, we did not use either method for our patients because they are sometimes associated with a risk of graft rejection and EBV-associated posttransplant lymphoproliferative disease (PTLD) when transplanting the immunodeficiency patients [11]. As GVHD in our series were relatively well controlled except for one case (Patient 2), we believe that HLAmatched unrelated donor marrow transplant can be safely performed without T-cell depletion or CD34-positive selection.…”
Section: Discussionmentioning
confidence: 99%
“…Another patient also suffered from pre-transplant complications involving the lung, but the failure was due to severe post-transplantation infection complicated with secondary graft failure and grade 4 acute GVHD. It has been observed that older patients with primary immunodeficiency disorders tend to be at higher risk for HSCT [11,20]. The reason for this is that they may have more severe pre-transplant infections and may have serious damage in critical organs such as lung and liver because of recurrent or persistent infections.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from their case, one more unmanipulated haplo-identical transplant was reported. There is a 4-5-fold increase in mortality after haploidentical compared to HLA-identical sibling grafts [7,11]. These reports show a high incidence of graft failure and poor immune reconstitution following T cell-depleted haploidentical HSCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is prudent to monitor levels and target the dose to achieve a steady state concentration of greater than 200 ng/ml to assure engraftment. It is determined that patient age, disease severity, and splenectomy did not affect outcome in HSCT of WAS patients in which HLA-identical sibling marrow grafts were used [7,8].…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] However, most patients lack matched sibling donors, and transplant using matched unrelated donors is effective only in a subset of patients. 6 Alternative methods, such as gene therapy, therefore warrant exploration.…”
Section: Introductionmentioning
confidence: 99%